A Comparative Study of EEG and aEEG in Seizure Diagnosis in Infants Admitted to the NICU - movahedi moghadam, elahe; Taghipour, Yalda; Shervin Badv, Reza; Kadivar, Maliheh; Sangsari , Raziyeh; Saeedi, Maryam; Ashrafi, MahmoudReza (Iranian Journal of Child Neurology, 2023)
Objectives Seizure is a common sign in neonates hospitalized in the neonatal intensive care units (NICU) that may lead to morbidity and mortality. Most neonatal seizures are subclinical. Conventional EEG (cEEG) is the gold standard for detecting and monitoring seizures but is not widely available. Amplitude-integrated electroencephalography (aEEG) has been used for over a decade to evaluate infants with seizures. In this study, we tried to determine the efficacy of aEEG as a widely available diagnostic tool in diagnosing seizures. Materials & Methods All cases with seizures or suspicious seizures were admitted to the NICU of the Children’s Medical Center for one year. cEEG and aEEG were performed for these infants. aEEG was recorded for at least six hours with a description of the tracing. Clinical information, outcomes, and questionnaires (patient information) were recorded in detail. The obtained data were analyzed with the SPSS version 24 software. Results Eleven out of twenty-five aEEG recordings were abnormal; other patients showed normal aEEGs. The most common clinical and neurological manifestations were seizure (68%) and hypotonia (28%); the mortality rate was 12%. No significant correlation was observed between aEEG findings and gender, age, familial relation, outcome, ultrasound result, type of seizure, and underlying disease.